FAKTOR YANG MEMENGARUHI PEMANFAATAN PELAYANAN KESEHATAN PADA MASYARAKAT MISKIN DI RSUD KABUPATEN NIAS TAHUN 2019 - Laoli, Hadirat Candra (JURNAL HEALTH REPRODUCTIVE, 2019)
Utilization of hospital services in Indonesia, especially for the poor is still not optimal, this is due to several factors that do not allow the public to utilize health services in hospitals. This study aims to determine the effect of knowledge, information, cost, transportation, service availability, speed and personnel services and family support on health services utilization in hospitals.This type of this study was survey quantitative methods used cross-sectional approach. The number of samples of 92 respondents who used reference had been taken proportionally and then selected using simple random sampling technique. Data were collected using a questionnaire that has been tested for validity and reliability with a total of 66 question questions. Statistical test of each variable with the use of health used chi-square with a significant level of 95% while the most influential variables are tested with logistic regression with a significant level of 95%.The results showed that there were people who did not utilize health services in hospitals. Based on the results of statistical tests found that there are two factors that most influence of health services utilization in hospitals, namely knowledge (p=.03) and family support (p=.00).It is recommended to the Nias District Government to monitor health programs aimed in increasing family and community knowledge in efforts to utilize health services. It is recommended for the Nias District Health Office to be more active in providing health education by collaborating with hospitals and puskesmas in the Nias District area